Oxidative phosphorylation in creatine transporter deficiency. (29th September 2020) - Li, Shizhe; Bianconi, Simona; van der Veen, Jan Willem; Dang Do, An; Stolinski, JoEllyn; Cecil, Kim M.; Hannah‐Shmouni, Fady; Porter, Forbes D.; Shen, Jun
Abstract : X‐linked creatine transporter deficiency (CTD) is one of the three types of cerebral creatine deficiency disorders. CTD arises from pathogenic variants in the X‐linked gene SLC6A8. We report the first phosphorus ( 31 P) MRS study of patients with CTD, where both phosphocreatine and total creatine concentrations were found to be markedly reduced. Despite the diminished role of creatine and phosphocreatine in oxidative phosphorylation in CTD, we found no elevation of lactate or lowered pH, indicating that the brain energy supply still largely relied on oxidative metabolism. Our results suggest that mitochondrial function is a potential therapeutic target for CTD. Abstract : We report the first phosphorus ( 31 P) MRS study of patients with creatine transporter deficiency. Both phosphocreatine and total creatine concentrations were found to be markedly reduced in the patients. This was accompanied by normal pH values and no elevation of the glycolytic product lactate, indicating that the brain energy supply remains dominated by oxidative phosphorylation in creatine transporter deficiency.